ANALYSIS OF ANXIETY FACTORS OF PREGNANT WOMEN ON SEXUAL RELATIONS IN TAMBELANG HEALTH CENTER, BEKASI DISTRICT, 2023 - Mujayanah, Yoyoh; Putri, Dian Priharja (HEARTY, 2025)
Background:Sexual intercourse is a primary need for married couples and can be carried out during pregnancy as long as no problems are found. However, some couples feel anxious about sexual relations during pregnancy. Anxiety during pregnancy is also related to emotional problems, hyperactivity disorders and impaired cognitive development in children. Research purposes: This research was conducted to determine the factors that cause anxiety among pregnant women regarding sexual relations at the Tambelang Community Health Center, Bekasi Regency in 2023. Research methods: This research is a quantitative study with a cross sectional design. This research was conducted at the Tambelang Community Health Center in December 2023-January 2024. The sample size was 130 pregnant women taken using accidental sampling technique. The factors that cause anxiety among pregnant women regarding sexual relations studied are age, gestational age, parity, experience of abortion, education, employment, and the mother's knowledge of sexual relations during pregnancy. Mother's knowledge was measured using a questionnaire and anxiety levels were measured usingHamilton Anxiety Rating Scale(HARS). Data analysis used the Chi Square test. Research results: Maternal age (p=0.012), gestational age (p=0.000), abortion experience (p=0.001), and knowledge (p=0.000) have significance values below 0.005, which means there is significant relationship between these factors and pregnant women's anxiety about sexual relations. Meanwhile, parity (p=0.386), last education (p=0.386) and employment (p=0.367) have significance values above 0.005, which means there is no significant relationship between these factors and pregnant women's anxiety about sexual relations. Conclusions and recommendations: Age, gestational age, abortion experience, and maternal knowledge have an influence on the level of anxiety of pregnant women regarding sexual relations at the Tambelang Community Health Center, Bekasi Regency in 2023. Meanwhile, parity, recent education, and employment have no influence on the level of anxiety of pregnant women. pregnant during sexual intercourse at the Tambelang Community Health Center, Bekasi Regency in 2023. The need to provide education to pregnant women regarding the impact of anxiety on sexual relations during pregnancy and how to prevent it.